A survey on cyber-crime prediction techniques - Shaerpour, Kaveh; Dehghantanha, Ali; Mahmod, Ramlan (Advanced Institute of Convergence Information Technology, 2013)
This paper is a review paper of journal and conference papers published in the field of crime prediction. Crime prediction is a growing field in the field of prediction. More and more law enforcement agencies are using or going to implement crime prediction software. In this paper firstly,data collection methods and findings of this paper are described and afterward the collected papers are described and their methods and findings are explained.